Accelerated Whole-Heart Coronary Imaging using Multiple Breath-holds and Compressed Sensing Monitored by Self-navigation - Forman, Christoph; Piccini, Davide; Hutter, Jana; Grimm, Robert; Hornegger, Joachim; Zenge, Michael O. (Proceedings of the 20th Annual Meeting of ISMRM, 2012)

Alae Tracker: Tracking of the Nasal Walls in MR-Imaging - Breininger, Katharina; Maier, Andreas; Forman, Christoph; Flatz, Wilhelm; Messmer, Catalina; Schuster, Maria (Bildverarbeitung für die Medizin 2014, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.alaetr
Keywords: tracking; nose; MRI

Automatic Bolus Analysis for DCE-MRI Using Radial Golden-Angle Stack-of-stars GRE Imaging - Grimm, Robert; Li, Feng; Forman, Christoph; Hutter, Jana; Kiefer, Berthold; Hornegger, Joachim; Block, Kai Tobias (International Society for Magnetic Resonance in Medicine, 2013)

Automatic Removal of Externally Attached Fiducial Markers in Cone Beam C-arm CT - Berger, Martin; Forman, Christoph; Schwemmer, Chris; Choi, Jang-Hwan; Müller, Kerstin; Maier, Andreas; Hornegger, Joachim; Fahrig, Rebecca (Bildverarbeitung für die Medizin 2014, 2014)
In computed tomography fiducial markers are frequently used to obtain accurate point correspondences for further processing. These markers typically cause metal artefacts, decreasing image quality of the subsequent reconstruction and are therefore often removed from the projection data. The placement of such markers is usually done on a surface, separating two materials, e.g. skin and air. Hence, a correct restoration of the occluded area is difficult. In this work six state-of-the-art interpolation techniques for the removal of high-density fiducial markers from cone-beam CT projection data are compared. We conducted a qualitative and quantitative evaluation for the removal of such markers and the ability to reconstruct the adjoining edge. Results indicate that an iterative spectral deconvolution is best suited for this application, showing promising results in terms of edge, as well as noise restoration.
UnivIS-Import:2015-07-08:Pub.2014.tech.IMMD.IMMD5.automa_5
Keywords: GRK-1773; Interpolation; C-arm CT; Metal Artifact

Comparison of Image-Based Retrospective and Optical Prospective Motion Correction for Diffusion Tensor Imaging - Aksoy, Murat; Forman, Christoph; Straka, Matus; Holdsworth, Samantha; Skare, Stefan; Hornegger, Joachim; Bammer, Roland (Proceedings of the ISMRM Workshop on Current Concepts of Motion Correction for MRI & MRS, 2010)

CoroEval: a multi-platform, multi-modality tool for the evaluation of 3D coronary vessel reconstructions - Schwemmer, Chris; Forman, Christoph; Wetzl, Jens; Maier, Andreas; Hornegger, Joachim (Physics in Medicine and Biology, 2014)
With default settings, measurements are taken at 1 mm intervals along the vessel centreline and from 10 different angles at each measurement point. This allows for outlier detection and noise-robust measurements without the burden and subjectivity a manual measurement process would incur. Graphical measurement results can be directly exported to vector or bitmap graphics for integration into scientific publications. Centreline and lumen segmentations can be exported as point clouds and in various mesh formats. We evaluated the diameter measurement process using three phantom datasets. An average deviation of 0.03 +/- 0.03 mm was found.
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD5.coroev
Keywords: medical imaging; coronary vessels; evaluation; software

Extending the Tracking Range for Prospective Motion Correction using a Single In-bore Camera and the Self-Encoded Marker - Forman, Christoph; Aksoy, Murat; Straka, Matus; Hornegger, Joachim; Bammer, Roland (Proceedings of the ISMRM Workshop on Current Concepts of Motion Correction for MRI & MRS, 2010)

Fast Automatic Coil Selection for Radial Stack-of-stars GRE Imaging - Grimm, Robert; Forman, Christoph; Hutter, Jana; Kiefer, Berthold; Hornegger, Joachim; Block, Kai Tobias (Proceedings of International Society for Magnetic Resonance in Medicine, 2013)

Fast Cross-Calibration Between MR Scanner and Optical System for Prospective Motion Correction - Aksoy, Murat; Forman, Christoph; Straka, Matus; Holdsworth, Samantha; Skare, Stefan; Hornegger, Joachim; Bammer, Roland (Proceedings of the 18th Annual Meeting of ISMRM & ESMRMB, 2010)

Fast Interpolation of Dense Motion Fields from Synthetic Phantoms - Maier, Andreas; Taubmann, Oliver; Wetzl, Jens; Wasza, Jakob; Forman, Christoph; Fischer, Peter; Hornegger, Joachim; Fahrig, Rebecca (Bildverarbeitung für die Medizin 2014, 2014)
Numerical phantoms are a common tool for the evaluation of registration and reconstruction algorithms. For applications concerning motion, dense deformation fields are of particular interest. Phantoms, however, are often described as surfaces and thus motion vectors can only be generated at these surfaces. In order to create dense motion fields, interpolation is required. A frequently used method for this purpose is the Parzen interpolator. However, with a high number of surface motion vectors and a high voxel count, its run time increases dramatically. In this paper, we investigate different methods to accelerate the creation of these motion fields using hierarchical sampling and the random ball cover. In the results, we show that a 643 volume can be sampled in less than one second with an error below 0.1 mm. Furthermore, we accelerate the interpolation of a 2563 dense deformation field to only 6.5 minutes using the proposed methods from days with previous methods.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.fastin_7
Keywords: interpolation; motion field; phantom

Free-Breathing, Self-Navigated and Dynamic 3-D Multi-Contrast Cardiac CINE Imaging Using Cartesian Sampling and Compressed Sensing - Hoppe, Elisabeth; Wetzl, Jens; Forman, Christoph; Koerzdoerfer, Gregor; Schneider, Manuel; Speier, Peter; Schmidt, Michaela; Maier, Andreas (Proceedings of the Joint Annual Meeting ISMRM-ESMRMB (27th Annual Meeting & Exhibition), 2019)
We present a free-breathing multi-contrast 3-D cardiac CINE acquisition and reconstruction technique based on Compressed Sensing. Inversion pulses were repeatedly applied during a continuous acquisition to sample contrast- and cardiac-resolved 3-D data, while a self-navigation method was applied for respiratory gating. Validation was performed in a phantom, showing recovery curves and T1* maps in good correlation to known T1 values for the phantom as well as a MOLLI reference measurement. Feasibility for in-vivo application was demonstrated in a healthy voluntee
Keywords: Magnetic Resonance Imaging; Cardiac CINE Magnetic Resonance Imaging; Multicontrast Imaging; Compressed Sensing

Free-Breathing Whole-Heart Coronary MRA: Motion Compensation Integrated into 3D Cartesian Compressed Sensing Reconstruction - Forman, Christoph; Grimm, Robert; Hutter, Jana; Maier, Andreas; Hornegger, Joachim; Zenge, Michael O. (MICCAI 2013, Part II, LNCS 8150, 2013)

Free-Breathing Whole-Heart Coronary MRI: An Image-Based Motion Compensation Integrated Into Compressed-Sensing Reconstruction - Forman, Christoph; Grimm, Robert; Hutter, Jana; Wasza, Jakob; Kraus, Martin; Hornegger, Joachim; Zenge, Michael O. (Proceedings of the 21st Annual Meeting of ISMRM, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD5.freebr_2

Fully automatic segmentation of left ventricular anatomy in 3-DLGE-MRI - Kurzendorfer, Tanja; Forman, Christoph; Schmidt, Michaela; Tillmanns, Christoph; Maier, Andreas; Brost, Alexander (Computerized Medical Imaging and Graphics, 2017)
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.fullya_0

Highly undersampled peripheral Time-of-Flight magnetic resonance angiography: optimized data acquisition and iterative image reconstruction - Hutter, Jana; Grimm, Robert; Forman, Christoph; Hornegger, Joachim; Schmitt, Peter (Magnetic Resonance Materials in Physics Biology and Medicine, 2015)
Object: The aim of this study was to investigate the acceleration of peripheral Time-of-Flight magnetic resonance angiography using Compressed Sensing and parallel magnetic resonance imaging (MRI) while preserving image quality and vascular contrast.
UnivIS-Import:2015-07-08:Pub.2015.tech.IMMD.IMMD5.highly
Keywords: Compressed Sensing; Iterative reconstruction; Non-contrast-enhanced MRA; Peripheral angiography

Highly undersampled time resolved phase-contrast MRA with flow-adapted compressed sensing reconstruction - Hutter, Jana; Greiser, Andreas; Grimm, Robert; Forman, Christoph; Hornegger, Joachim; Schmitt, Peter (Proceedings of the 21st Annual meeting of the ISMRM, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD5.highly

High-Resolution 3D Whole-Heart Coronary MRA: A Study on the Combination of Data Acquisition in Multiple Breath-Holds and 1D Residual Respiratory Motion Compensation - Forman, Christoph; Piccini, Davide; Grimm, Robert; Hutter, Jana; Hornegger, Joachim; Zenge, Michael O. (Magnetic Resonance Materials in Physics Biology and Medicine, 2014)
Object: To study a scan protocol for coronary magnetic resonance angiography based on multiple breath-holds featuring 1D motion compensation and to compare the resulting image quality to a navigator-gated free-breathing acquisition. Image reconstruction was performed using L1 regularized iterative SENSE. Materials and methods: The effects of respiratory motion on the Cartesian sampling scheme were minimized by performing data acquisition in multiple breath-holds. During the scan, repetitive readouts through a k-space center were used to detect and correct the respiratory displacement of the heart by exploiting the self-navigation principle in image reconstruction. In vivo experiments were performed in nine healthy volunteers and the resulting image quality was compared to a navigator-gated reference in terms of vessel length and sharpness. Results: Acquisition in breath-hold is an effective method to reduce the scan time by more than 30 % compared to the navigator-gated reference. Although an equivalent mean image quality with respect to the reference was achieved with the proposed method, the 1D motion compensation did not work equally well in all cases. Conclusion: In general, the image quality scaled with the robustness of the motion compensation. Nevertheless, the featured setup provides a positive basis for future extension with more advanced motion compensation methods. © 2014 ESMRMB.
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD5.highre
Keywords: Compressed sensing; Coronary magnetic resonance angiography; Multiple breath-holds; Respiratory motion compensation

Hybrid prospective and retrospective head motion correction to mitigate cross-calibration errors - Aksoy, Murat; Forman, Christoph; Straka, Matus; Cukur, Tolga; Hornegger, Joachim; Bammer, Roland (Magnetic Resonance in Medicine, 2012)
Utilization of external motion tracking devices is an emerging technology in head motion correction for MRI. However, cross-calibration between the reference frames of the external tracking device and the MRI scanner can be tedious and remains a challenge in practical applications. In this study, we present two hybrid methods, both of which combine prospective, optical-based motion correction with retrospective entropy-based autofocusing to remove residual motion artifacts. Our results revealed that in the presence of cross-calibration errors between the optical tracking device and the MR scanner, application of retrospective correction on prospectively corrected data significantly improves image quality. As a result of this hybrid prospective and retrospective motion correction approach, the requirement for a high-quality calibration scan can be significantly relaxed, even to the extent that it is possible to perform external prospective motion tracking without any prior cross-calibration step if a crude approximation of cross-calibration matrix exists. Moreover, the motion tracking system, which is used to reduce the dimensionality of the autofocusing problem, benefits the retrospective approach at the same time. Copyright © 2011 Wiley Periodicals, Inc.

Hybrid Prospective & Retrospective Head Motion Correction System to Mitigate Cross-Calibration Errors - Aksoy, Murat; Forman, Christoph; Holdsworth, Samantha; Skare, Stefan; Hornegger, Joachim; Bammer, Roland (Proceedings of the 18th Annual Meeting of ISMRM & ESMRMB, 2010)

Improved Pose Detection for Single Camera Real-Time MR Motion Correction Using a Self-Encoded Marker - Forman, Christoph; Aksoy, Murat; Straka, Matus; Hornegger, Joachim; Bammer, Roland (Proceedings of the 18th Annual Meeting of ISMRM & ESMRMB, 2010)

Improved Prospective Optical Motion Correction for DTI Using an Extended-Field-of-View and Self-Encoded Marker - Aksoy, Murat; Forman, Christoph; Straka, Matus; Holdsworth, Samantha; Skare, Stefan; Santos, Juan; Hornegger, Joachim; Bammer, Roland (Proceedings of the 18th Annual Meeting of ISMRM & ESMRMB, 2010)

Inverse root sampling pattern for iterative reconstruction in non-CE MR angiography - Hutter, Jana; Grimm, Robert; Forman, Christoph; Hornegger, Joachim; Schmitt, Peter (Magnetic Resonance Materials in Physics, Biology and Medicine, 2011)

Isotropic 3-D CINE Imaging with Sub-2mm Resolution in a Single Breath-Hold - Wetzl, Jens; Schmidt, Michaela; Zenge, Michael O.; Lugauer, Felix; Lazar, Laszlo; Nadar, Mariappan; Maier, Andreas; Hornegger, Joachim; Forman, Christoph (Proceedings of the 23rd Annual Meeting of the ISMRM (ISMRM 2015), 2015)
UnivIS-Import:2015-07-08:Pub.2015.tech.IMMD.IMMD5.isotro

Iterative Reconstruction Methods to Reduce Respiratory Motion Artifacts in Cartesian Coronary MRI - Forman, Christoph (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2017)
Cardiovascular diseases and coronary artery disease (CAD) in particular are the leading cause of death in most developed countries worldwide. Although CAD progresses slowly over several years, it often remains unnoticed and may lead to myocardial infarction in a sudden event. For this reason, there is a strong clinical need for the development of non-invasive and radiation-free screening methods allowing for an early diagnosis of these diseases. In this context, magnetic resonance imaging (MRI) represents a promising imaging modality. However, the slow acquisition process and the consequent susceptibility to artifacts due to cardiac and respiratory motion are major challenges for coronary MRI and have so far hindered its routine application in clinical examinations. Commonly, respiratory motion is addressed during free-breathing acquisitions by gating the scan to a consistent respiratory phase in end-expiration with a navigator monitoring the patient's diaphragm. Acceptance rates below 40% lead to a prolonged total acquisition time that is also not predictable in advance. In this work, a novel variable-density spiral phyllotaxis pattern is introduced for free-breathing whole-heart coronary MRI. It provides an incoherent sub-sampling of the Cartesian phase-encoding plane and allows for highly accelerated data acquisition when combined with compressed sensing reconstruction. With this sampling pattern, sub-sampling rates up to 10.2 enable a significant reduction of the total acquisition time. Furthermore, this sampling pattern is well-prepared for respiratory self-navigation, which performs respiratory motion compensation solely relying on the acquired imaging data and promises full scan efficiency. In this context, a novel motion detection approach is proposed that provides a robust tracking of respiration. However, 1-D motion compensation based on respiratory self-navigation was found to be not always sufficient for Cartesian imaging. Hence, an alternative method is presented to reduce the effects of respiration following the concept of weighted iterative reconstruction. In this technique, inconsistencies introduced by respiratory motion during data acquisition are addressed by weighting the least squares optimization according to a data consistency measure that is obtained from respiratory self-navigation. This approach forms the basis for an extension to a motion-compensated reconstruction with a dense, non-rigid motion model. With the proposed method, motion-compensated reconstruction was enabled for the first time in 3-D whole-heart imaging without the need for either additional calibration data or manual user interaction. The techniques presented in this thesis were fully integrated in a clinical MR scanner and tested in 14 volunteers. These results were compared to a navigator-gated reference acquisition. The acquisition time of the navigator-gated reference acquisition of 10.1 ± 2.3 min was reduced by one third to 6.3 ± 0.9 min with the proposed method utilizing respiratory self-navigation. After motion-compensated reconstruction, assessment of image quality revealed no significant differences com- pared to the images of the reference acquisition. Vessel sharpness was measured as 0.44 ± 0.05 mm−1 and 0.45 ± 0.05 mm−1 for RCA, and 0.39 ± 0.04 mm−1 and 0.40 ± 0.05 mm−1 for LAD, respectively.<br
Keywords: 3D-Rekonstruktion; MRT; Medizinische Bildgebung; Bewegungskompensation

Low-rank and Sparse Matrix Decomposition for Compressed Sensing reconstruction of Magnetic Resonance 4D Phase Contrast blood flow imaging (LoSDeCoS 4D-PCI) - Hutter, Jana; Schmitt, Peter; Gunhild, Aandal; Greiser, Andreas; Forman, Christoph; Grimm, Robert; Hornegger, Joachim; Maier, Andreas (Proceedings of the Medical Image Computing and Computer-Assisted Intervention, 2013)

Minimization of Respiratory Motion Artifacts for Whole-Heart Coronary MRI: A Combination of Self-navigation and Weighted Compressed Sensing Reconstruction - Forman, Christoph; Piccini, Davide; Hutter, Jana; Grimm, Robert; Hornegger, Joachim; Zenge, Michael O. (Proceedings of International Society for Magnetic Resonance in Medicine, 2012)

Multi-Dimensional Flow-Adapted Compressed Sensing (MDFCS) for time-resolved velocity-encoded Phase Conrast MRA - Hutter, Jana; Grimm, Robert; Forman, Christoph; Greiser, Andreas; Hornegger, Joachim; Schmitt, Peter (Proceedings of the 10th IEEE International Symposium on Biomedical Imaging, 2013)

Multi-Dimensional Flow-Preserving Compressed Sensing (MuFloCoS) for Time-Resolved Velocity-Encoded Phase Contrast MRI - Hutter, Jana; Schmitt, Peter; Saake, Marc; Stübinger, Axel; Grimm, Robert; Forman, Christoph; Greiser, Andreas; Hornegger, Joachim; Maier, Andreas (IEEE Transactions on Medical Imaging, 2015)
4-D time-resolved velocity-encoded phase-contrast MRI (4-D PCI) is a fully non-invasive technique to assess hemodynamics in vivo with a broad range of potential applications in multiple cardiovascular diseases. It is capable of providing quantitative flow values and anatomical information simultaneously. The long acquisition time, however, still inhibits its wider clinical use. Acceleration is achieved at present using parallel MRI (pMRI) techniques which can lead to substantial loss of image quality for higher acceleration factors. Both the high-dimensionality and the significant degree of spatio-temporal correlation in 4-D PCI render it ideally suited for recently proposed compressed sensing (CS) techniques. We propose the Multi-Dimensional Flow-preserving Compressed Sensing (MuFloCoS) method to exploit these properties. A multi-dimensional iterative reconstruction is combined with an interleaved sampling pattern (I-VT), an adaptive masked and weighted temporal regularization (TMW) and fully automatically obtained vessel-masks. The performance of the novel method was analyzed concerning image quality, feasibility of acceleration factors up to 15, quantitative flow values and diagnostic accuracy in phantom experiments and an in vivo carotid study with 18 volunteers. Comparison with iterative state-of-the-art methods revealed significant improvements using the new method, the temporal normalized root mean square error of the peak velocity was reduced by 45.32% for the novel MuFloCoS method with acceleration factor 9. The method was furthermore applied to two patient cases with diagnosed high-grade stenosis of the ICA, which confirmed the performance of MuFloCoS to produce valuable results in the presence of pathological findings in 56 s instead of over 8 min (full sampling).
UnivIS-Import:2015-07-08:Pub.2015.tech.IMMD.IMMD5.multid
Keywords: Compressed sensing; hemodynamics; magnetic resonance imaging (MRI); phase contrast MRI

Novel Projection-Based Unsupervised Respiratory Motion Feedback for Free-Breathing Whole-Heart Coronary MR Imaging - Forman, Christoph; Piccini, Davide; Hornegger, Joachim; Zenge, Michael O. (Proceedings of the 21st Annual Meeting of ISMRM, 2013)

Prediction of Respiration-Induced Internal 3-D Deformation Fields From Dense External 3-D Surface Motion - Taubmann, Oliver; Wasza, Jakob; Forman, Christoph; Fischer, Peter; Wetzl, Jens; Maier, Andreas; Hornegger, Joachim (Proceedings of the 28th International Congress and Exhibition, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.predic_9
Keywords: Respiratory Motion; Motion Modeling; Motion Prediction; External Surrogate

Prediction of the Benefit of Motion-Compensated Reconstruction for Whole-Heart Coronary MRI - Wetzl, Jens; Forman, Christoph; Maier, Andreas; Hornegger, Joachim; Zenge, Michael O. (Proceedings of the 23rd Annual Meeting of the ISMRM (ISMRM 2015), 2015)
UnivIS-Import:2015-07-08:Pub.2015.tech.IMMD.IMMD5.predic

Prospective optical motion correction for 3D time-of-flight angiography - Kopeinigg, Daniel; Aksoy, Murat; Forman, Christoph; Straka, Matus; Seaman, Danielle; Rosenberg, Jarrett; Fleischmann, Dominik; Hornegger, Joachim; Bammer, Roland (Magnetic Resonance in Medicine, 2012)

Real-Time Optical Motion Correction for Diffusion Tensor Imaging - Aksoy, Murat; Forman, Christoph; Straka, Matus; Skare, Stefan; Holdsworth, Samantha; Hornegger, Joachim; Bammer, Roland (Magnetic Resonance in Medicine, 2011)
Head motion is a fundamental problem in brain MRI. The problem is further compounded in diffusion tensor imaging because of long acquisition times, and the sensitivity of the tensor computation to even small misregistration. To combat motion artifacts in diffusion tensor imaging, a novel real-time prospective motion correction method was introduced using an in-bore monovision system. The system consists of a camera mounted on the head coil and a self-encoded checkerboard marker that is attached to the patient's forehead. Our experiments showed that optical prospective motion correction is more effective at removing motion artifacts compared to image-based retrospective motion correction. Statistical analysis revealed a significant improvement in similarity between diffusion data acquired at different time points when prospective correction was used compared to retrospective correction (P < 0.001). © 2011 Wiley-Liss, Inc.
UnivIS-Import:2015-04-14:Pub.2011.tech.IMMD.IMMD5.realti
Keywords: motion; DTI; diffusion; real-time motion correction; optical motion correction; prospective motion correction

Reduction of Respiratory Motion Artifacts for Free-Breathing Whole-Heart Coronary MRA by Weighted Iterative Reconstruction - Forman, Christoph; Piccini, Davide; Grimm, Robert; Hutter, Jana; Hornegger, Joachim; Zenge, Michael O. (Magnetic Resonance in Medicine, 2014)
Purpose: To combine weighted iterative reconstruction with self-navigated free-breathing coronary magnetic resonance angiography for retrospective reduction of respiratory motion artifacts. Methods: One-dimensional self-navigation was improved for robust respiratory motion detection and the consistency of the acquired data was estimated on the detected motion. Based on the data consistency, the data fidelity term of iterative reconstruction was weighted to reduce the effects of respiratory motion. In vivo experiments were performed in 14 healthy volunteers and the resulting image quality of the proposed method was compared to a navigator-gated reference in terms of acquisition time, vessel length, and sharpness. Result: Although the sampling pattern of the proposed method contained 60% more samples with respect to the reference, the scan efficiency was improved from 39.5±10.1% to 55.1±9.1%. The improved self-navigation showed a high correlation to the standard navigator signal and the described weighting efficiently reduced respiratory motion artifacts. Overall, the average image quality of the proposed method was comparable to the navigator-gated reference. Conclusion: Self-navigated coronary magnetic resonance angiography was successfully combined with weighted iterative reconstruction to reduce the total acquisition time and efficiently suppress respiratory motion artifacts. The simplicity of the experimental setup and the promising image quality are encouraging toward future clinical evaluation. © 2014 Wiley Periodicals, Inc.
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD5.reduct
Keywords: Compressed sensing; Coronary magnetic resonance angiography; Motion suppression; Weighted iterative reconstruction

Self-Encoded Marker Design for Adaptive Optical Real-Time Motion Correction - Forman, Christoph; Aksoy, Murat; Straka, Matus; Hornegger, Joachim; Bammer, Roland (Proceedings of the 18th Annual Meeting of ISMRM & ESMRMB, 2010)

Self-encoded marker for optical prospective head motion correction in MRI - Forman, Christoph; Aksoy, Murat; Hornegger, Joachim; Bammer, Roland (Medical Image Analysis, 2011)
The tracking and compensation of patient motion during a magnetic resonance imaging (MRI) acquisition is an unsolved problem. For brain MRI, a promising approach recently suggested is to track the patient using an in-bore camera and a checkerboard marker attached to the patient's forehead. However, the possible tracking range of the head pose is limited by the fact that the locally attached marker must be entirely visible inside the camera's narrow field of view (FOV). To overcome this shortcoming, we developed a novel self-encoded marker where each feature on the pattern is augmented with a 2-D barcode. Hence, the marker can be tracked even if it is not completely visible in the camera image. Furthermore, it offers considerable advantages over the checkerboard marker in terms of processing speed, since it makes the correspondence search of feature points and marker-model coordinates, which are required for the pose estimation, redundant. The motion correction with the novel self-encoded marker recovered a rotation of 18° around the principal axis of the cylindrical phantom in-between two scans. After rigid registration of the resulting volumes, we measured a maximal error of 0.39 mm and 0.15° in translation and rotation, respectively. In in vivo experiments, the motion compensated images in scans with large motion during data acquisition indicate a correlation of 0.982 compared to a corresponding motion-free reference. © 2011 Elsevier B.V.

Self-encoded Marker for Optical Prospective Head Motion Correction in MRI - Forman, Christoph; Aksoy, Murat; Hornegger, Joachim; Bammer, Roland (Lecture Notes in Computer Science, 2010)

Self-gated MRI motion modeling for respiratory motion compensation in integrated PET/MRI - Grimm, Robert; Fürst, Sebastian; Souvatzoglou, Michael; Forman, Christoph; Hutter, Jana; Dregely, Isabel; Ziegler, Sibylle; Kiefer, Berthold; Hornegger, Joachim; Block, Kai Tobias; Nekolla, Stephan G. (Medical Image Analysis, 2015)
Accurate localization and uptake quantification of lesions in the chest and abdomen using PET imaging is challenged by respiratory motion occurring during the exam. This work describes how a stack-of-stars MRI acquisition on integrated PET/MRI systems can be used to derive a high-resolution motion model, how many respiratory phases need to be differentiated, how much MRI scan time is required, and how the model is employed for motion-corrected PET reconstruction. MRI self-gating is applied to perform respiratory gating of the MRI data and simultaneously acquired PET raw data. After gated PET reconstruction, the MRI motion model is used to fuse the individual gates into a single, motion-compensated volume with high signal-to-noise ratio (SNR). The proposed method is evaluated in vivo for 15 clinical patients. The gating requires 5-7 bins to capture the motion to an average accuracy of 2 mm. With 5 bins, the motion-modeling scan can be shortened to 3-4 min. The motion-compensated reconstructions show significantly higher accuracy in lesion quantification in terms of standardized uptake value (SUV) and different measures of lesion contrast compared to ungated PET reconstruction. Furthermore, unlike gated reconstructions, the motion-compensated reconstruction does not lead to SNR loss.
UnivIS-Import:2015-03-09:Pub.2015.tech.IMMD.IMMD5.selfga
Keywords: Motion compensation; MRI; PET/MRI; Respiratory gating; Respiratory motion

Self-Gated Radial MRI for Respiratory Motion Compensation on Hybrid PET/MR Systems - Grimm, Robert; Fürst, Sebastian; Dregely, Isabel; Forman, Christoph; Hutter, Jana; Ziegler, Sibylle; Nekolla, Stephan G.; Kiefer, Berthold; Schwaiger, Markus; Hornegger, Joachim; Block, Kai Tobias (Proceedings of the 16th International Conference on Medical Image Computing and Computer Assisted Intervention, 2013)

Self-gating Reconstructions of Motion and Perfusion for Free-breathing T1-weighted DCE-MRI of the Thorax Using 3D Stack-of-stars GRE Imaging - Grimm, Robert; Block, Kai Tobias; Hutter, Jana; Forman, Christoph; Hintze, Christian; Kiefer, Berthold; Hornegger, Joachim (Proceedings of International Society for Magnetic Resonance in Medicine, 2012)

Single-breath-hold abdominal T1 mapping using 3D Cartesian Look-Locker with spatiotemporal sparsity constraints - Lugauer, Felix; Wetzl, Jens; Forman, Christoph; Schneider, Manuel; Kiefer, Berthold; Hornegger, Joachim; Nickel, Dominik; Maier, Andreas (Magnetic Resonance Materials in Physics Biology and Medicine, 2018)
UnivIS-Import:2018-09-05:Pub.2018.tech.IMMD.IMMD5.single
Keywords: T1 mapping; 3D Look-Locker; Compressed Sensing; Poisson Sampling

Single Breath-Hold Abdominal T1 Mapping Using 3-D Cartesian Sampling and Spatiotemporally Constrained Reconstruction - Lugauer, Felix; Wetzl, Jens; Forman, Christoph; Schneider, Manuel; Kiefer, Berthold; Nickel, Dominik; Maier, Andreas (Proceedings of the 25th Annual Meeting of the ISMRM (ISMRM 2017), 2017)
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD5.single_2
Keywords: Volumetric T1 mapping; Look-Locker; Compressed Sensing

ToF/RGB Sensor Fusion for 3-D Endoscopy - Haase, Sven; Forman, Christoph; Kilgus, Thomas; Bammer, Roland; Maier-Hein, Lena; Hornegger, Joachim (Current Medical Imaging Reviews, 2013)

ToF/RGB Sensor Fusion for Augmented 3-D Endoscopy using a Fully Automatic Calibration Scheme - Haase, Sven; Forman, Christoph; Kilgus, Thomas; Bammer, Roland; Maier-Hein, Lena; Hornegger, Joachim (Bildverarbeitung für die Medizin, 2012)

Variable Temporal Resolution Reconstruction for Golden-Angle Radial Sparse Parallel DCE-MRI - Grimm, Robert; Nickel, Dominik; Hutter, Jana; Forman, Christoph; Kiefer, Berthold; Hornegger, Joachim; Block, Kai Tobias (Proceedings of the 22nd Annual Meeting of the ISMRM, 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.variab

Vessel Adapted Regularization for Iterative Reconstruction in MR Angiography - Hutter, Jana; Grimm, Robert; Forman, Christoph; Hornegger, Joachim; Schmitt, Peter (Proceedings of the 20th Annual Meeting of ISMRM, 2012)